CLINICAL SPECTRUM, FUNCTIONAL SEVERITY AND NEUROIMAGING CORRELATES IN CHILDREN WITH CEREBRAL PALSY (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Cerebral palsy (CP) encompasses a heterogeneous group of neurodevelopmental disorders characterized by aberrant motor function and posture, often accompanied by sensory, cognitive and communicative impairments. Although not part of the CP definition, magnetic resonance imaging (MRI) sheds light on the localization, nature, and severity of brain compromise. This study aims to provide a comprehensive description of the clinical and neuroimaging characteristics of children with CP, highlighting the distribution of functional abilities and neuroimaging findings. Methods: The present study was conducted at the Department of Pediatrics, Govt. Medical College Jammu over a period of one year with effect from September 2022 to August 2023 and included 45 patients with cerebral palsy. Data on clinical profile, functional status, and MRI findings were collected and analyzed. Results: At 5 minutes, 44.4% of patients had APGAR scores of 4-6, 28.9% had scores of 7 or above, and 2.2% had scores below 4. At 10 minutes, 40% had scores of 4-6 and 35% had scores of 7 or above. 46.7% of patients required resuscitation, with 52.4% needing bag and mask ventilation. Spastic quadriplegia was the most common type of CP (51.1%), followed by diplegia (28.9%), hemiplegia (11.1%), dyskinetic (6.7%), and ataxic (2.2%) forms. Most patients had severe functional limitations, with GMFCS Grade V (35.6%), MACS Grade IV (28.9%), CFCS Grade IV (33.3%), and EDACS Grade IV (35.6%) being most common. MRI findings showed periventricular leukomalacia (PVL) in 37.8%, cortico-subcortical lesions in 24.4%, and basal ganglia/thalamus injury in 17.8% of patients. Conclusion: The study highlights the importance of early identification and intervention in cerebral palsy, with most patients presenting with severe functional limitations and abnormal MRI findings, emphasizing the need for standardized assessment and management protocols.